2014
DOI: 10.1017/langcog.2014.5
|View full text |Cite
|
Sign up to set email alerts
|

That-variation in German and Spanish L2 English

Abstract: In certain English finite complement clauses, inclusion of the complementizer that is optional. Previous research has identified various factors that influence when native speakers tend to produce or omit the complementizer, including syntactic weight, clause juncture constraints, and predicate frequency. The present study addresses the question to what extent German and Spanish learners of English as a second language (L2) produce and omit the complementizer under similar conditions. 3,622 instances of Englis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…Jones & Tagliamonte 2004;Tagliamonte & Smith 2005;Tagliamonte 2014, among many other studies), but also in other schools of variation study (e.g. Bresnan & Hay 2008;Bresnan & Ford 2010;Ehret, Wolk & Szmrecsanyi 2014;Gries & Deshors 2014;Wulff, Lester & Martinez-Garcia 2014;Hinrichs, Szmrecsanyi & Bohmann 2015). But it is only in recent years that the predictions outlined in the previous paragraph have begun to be explored more systematically.…”
Section: Introductionmentioning
confidence: 97%
“…Jones & Tagliamonte 2004;Tagliamonte & Smith 2005;Tagliamonte 2014, among many other studies), but also in other schools of variation study (e.g. Bresnan & Hay 2008;Bresnan & Ford 2010;Ehret, Wolk & Szmrecsanyi 2014;Gries & Deshors 2014;Wulff, Lester & Martinez-Garcia 2014;Hinrichs, Szmrecsanyi & Bohmann 2015). But it is only in recent years that the predictions outlined in the previous paragraph have begun to be explored more systematically.…”
Section: Introductionmentioning
confidence: 97%
“…German influence on L3 English can be seen as preventing or diminishing the effect of negative transfer from L1 Catalan and L2 Spanish. Moreover, transfer from German can be related to the typological proximity between the two Germanic languages-German and English-and support the Typological Primacy Model of the initial stages in L3 acquisition outlined by Rothman In a different study, Wulff et al (2014) analyzed a corpus of data with the aim of determining if learners are sensitive to the many factors (see Section 2) that determine native speakers' choices in the production of the null that. Apart from direct object clauses, which are the ones we consider in our experiment, Wulff et al (2014) study also analyzed other contexts where the null that is allowed.…”
Section: The Null That and Second Language Acquisitionmentioning
confidence: 73%
“…There is not much research on the L2 knowledge and performance of the null that. The few existing studies have found that the native languages of learners influence their L2 production Wulff et al 2014). There may also be transfer from a subsequently learned language on the production of the null that to a previously acquired language (Llinàs-Grau and Mayenco 2016).…”
Section: The Null That and Second Language Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach allows one to see whether X 1 , X 2 , …, X n behave differently depending on L1 or VARIETY (see Gries and Deshors 2014: Section 3), which is often the main question of such studies (even if this is often not discussed using the above kind of statistical-interaction terminology). As mentioned above, such studies are becoming increasingly widespread; examples include but are not limited to Deshors (2014Deshors ( , 2018, Wulff et al (2014), , Szmrecsanyi et al (2017). In spite of the fact that these studies are a huge improvement over decades of monofactorial chisquared or loglikelihood ratio tests, depending on one's perspective, Gries and Deshors (2014) and Gries and Adelman (2014) developed an alternative approach that has a slightly different focus.…”
Section: General Introductionmentioning
confidence: 99%